Unconjugated Bilirubin Attenuates DSS-Induced Colitis Potentially via Enhancement of Bilirubin Reabsorption - Zhao, Chong; Huang, Hongli; Pan, Qiuhua; Huang, Wenqi; Peng, Wu; Xu, Haoming; Feng, Zhiqiang; Du, Yanlei; Nie, Yuqiang; Zhou, Yongjian (Frontiers in Pharmacology, 2021)
Studies increasingly show that ulcerative colitis (UC) is a consequence of an imbal-ance between oxidative stress and antioxidant capacity. Bilirubin exerts an anti-inflammatory effect by scavenging reactive oxygen species (ROS), although the exact mechanism is not completely understood. The aim of this study was to determine the role of serum bilirubin in UC using patient data and a mouse model of dextran sodium sulfate (DSS)-induced colitis. We found that low levels of serum bilirubin correlated to a higher risk of UC in a retrospective case-control population. Pre-treatment with exogenous unconjugated bilirubin (UCB) significantly enhanced colonic bilirubin absorption in mice, and attenuated the DSS-induced body weight loss, colon shortening and histopathological damage. Mechanistically, bilirubin prevented the infiltration of inflammatory cells, and decreased the levels of myeloperoxidase and pro-inflammatory cytokines in the serum and colon. Moreover, bilirubin inhibited ROS and malondialdehyde production, scavenged superoxide anions (O2.-) from the colon and enhanced the total antioxidant capacity. In conclusion, exogenous UCB attenuated DSS-induced colitis by directly scavenging O2.- and enhancing bilirubin reabsorption in the colon via enterohepatic cycling.